Gas chromatography with parallel hard and soft ionization mass spectrometry1. (15th January 2015) - Hejazi, Leila; Guilhaus, Michael; Hibbert, D. Brynn; Ebrahimi, Diako
<x xml:space="preserve">Abstract</x> RATIONALE Mass spectrometric identification of compounds in chromatography can be obtained from molecular masses from soft ionization mass spectrometry techniques such as field ionization (FI) and fragmentation patterns from hard ionization techniques such as electron ionization (EI). Simultaneous detection by EI and FI mass spectrometry allows alignment of the different information from each method. METHODS We report the construction and characteristics of a combined instrument consisting of a gas chromatograph and two parallel mass spectrometry ionization sources, EI and FI. When considering both ion yield and signal‐to‐noise it was postulated that good‐quality EI and FI mass spectra could be obtained simultaneously using a post‐column splitter with a split fraction of 1:10 for EI/FI. This has been realised and we report its application for the analysis of several complex mixtures. RESULTS The differences between the full width at half maximum (FWHM) of the EI and FI chromatograms were statistically insignificant, and the retention times of the chromatograms were highly correlated (r2 =0.9999) with no detectable bias. The applicability and significance of this combined instrument and the attendant methodology are illustrated by the analysis of standard samples of 13 compounds with diverse structures, and the analysis of mixtures of fatty acids, fish oil, hydrocarbons and yeast metabolites. CONCLUSIONS This combined dual‐source instrument saves time and resources, and more importantly generates equivalent chromatograms aligned in time, in EI and FI (i.e. peaks with similar shapes and identical positions). The identical FWHMs and retention times of the EI and FI chromatograms in this combined instrument enable the accurate assignment of fragment ions from EI to their corresponding molecular ions in FI. Copyright © 2014 John Wiley & Sons, Ltd.